2005
DOI: 10.5194/aab-48-518-2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage period and egg weight of Japanese quail eggs on hatching results (short communication)

Abstract: This study was undertaken to determine the effects of storage period and egg weight of hatching eggs of Japanese quails on fertility, hatchability results. Eggs were obtained 150 females quails, all at 15 weeks of age. A total of 1942 hatching eggs were separated into 3 groups as light-weight (9.50-10.50 g), medium-weight (10.51-11.50 g), and heavy-weight (11.51-12.50 g). Based on storage period, eggs were divided into 5 groups as group 1 (0-3 days), group 2 (4-6 days), group 3 (7-9 days), group 4 (10-12 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 12 publications
5
18
4
1
Order By: Relevance
“…However, there was no significant (P>0.05) difference between the medium and lowest egg sized group in the regard (Table 1). This finding is in agreement with the experiment conducted in Turkey by Seker et al, (2005) that the embryo mortality rate of lightest (9.50-10.50 g) egg size group was higher than of medium and largest egg size groups, indicating that embryonic mortality decreases as the egg weight increases. This situation may be explained as heavy weight eggs have sufficient nutrients and centrally placed yolk to support embryonic growth and development compared to light weight eggs (Sekeret al, 2005).…”
Section: Effect Of Egg Size On Embryo Mortality Ratesupporting
confidence: 82%
See 2 more Smart Citations
“…However, there was no significant (P>0.05) difference between the medium and lowest egg sized group in the regard (Table 1). This finding is in agreement with the experiment conducted in Turkey by Seker et al, (2005) that the embryo mortality rate of lightest (9.50-10.50 g) egg size group was higher than of medium and largest egg size groups, indicating that embryonic mortality decreases as the egg weight increases. This situation may be explained as heavy weight eggs have sufficient nutrients and centrally placed yolk to support embryonic growth and development compared to light weight eggs (Sekeret al, 2005).…”
Section: Effect Of Egg Size On Embryo Mortality Ratesupporting
confidence: 82%
“…However, there was insignificant (P> 0.05) difference between intermediate and longest egg storage period group in this regard (Table 3). This result was consistent with the experiment carried out in Turkey by Seker et al, (2005) who noticed that there was highly significant (P< 0.01) difference between the effect of storage period (≤3 days, 4-6 days, 7-9 days, 10-12 days and 13-15 days) on embryo mortality rates. Similarly, the result reported by Lacin et al, (2008) tells that the storage period (1-3 days, 6-8 days and 12-14 days) had highly significant (P< 0.01) effect on early death rates and interaction between egg storage period groups was significant (P< 0.05).…”
Section: Effect Of Age Of Hen On Hatchability Ratesupporting
confidence: 81%
See 1 more Smart Citation
“…Fasenko et al (2001a) observed 87.5% and 70.5% hatchability in chicken eggs stored at 11.5°C for four and 14 days, respectively, and 70.42% and 65.6% hatchability in turkeys eggs stored at 17.4°C for the same periods (Fasenko et al, 2001b). Seker et al (2005) stored Japanese quail eggs between 9 to 12 °C and 70-75% relative humidity for 15 days and obtained 90. 00, 88.74, 67.96, 72.45, and 50.31% in eggs stored up to three days, 4-6 days, 7-9 days, 10-12 days, and 13-15 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Porém outros autores afirmam que o peso do ovo é o fator dominante na determinação do peso ao nascer (SILVERSIDES; SCOTT, 2001;TONA et al, 2002).…”
Section: Resultsunclassified